The shape of water [videorecording (DVD)] - Toro, Guillermo del, 1964-; Hawkins, Sally, 1976-; Spencer, Octavia; Shannon, Michael, 1974- (Twentieth Century Fox Home Entertainment, 2018)
An otherworldly fairy tale, set against the backdrop of Cold War-era America circa 1962. In the hidden high-security government laboratory where she works, lonely Elisa is trapped in a life of isolation. Elisa's life is changed forever when she and co-worker Zelda discover a secret classified experiment.